ESTADO BRASILEIRO E POVOS INDÍGENAS: direito aos territórios tradicionais dos Guarani Kaiowá na fronteira Brasil-Paraguai do Mato Grosso do Sul - Elvis Gomes Marques Filho (2022)
The present dissertation has the general objective of analyzing the guarantee of human and fundamental rights of the Guarani Kaiowá indigenous peoples in the processes of demarcation of their territories, in the border region between Brazil and Paraguay, in Mato Grosso do Sul. The specific objectives are to understand the definition of traditional territories of indigenous peoples; identify national and international laws that guarantee the territorial rights of indigenous peoples; and to point out human rights violations against indigenous peoples in the demarcation of their traditional territories by the State. As for the research problem, I seek to answer: what are the consequences of violations of human and fundamental rights to the traditional territory and culture of the Guarani Kaiowá by the Brazilian and Paraguayan states, in the border region of Mato Grosso do Sul? Based on this, the hypothesis raised is that these violations cause the extermination and ethnocide of the Guarani Kaiowá, especially in situations of territorial conflicts. For that, we resort to bibliographic, documentary and intermittent field research, using the hypothetical-deductive method. Through a qualitative approach and descriptive-exploratory research, with photoethnography, this research achieved the expected results. The research has as main object of study the Guarani Kaiowá indigenous peoples, from the tekoha Ñande Ru Marangatu, in Antônio João, located in the state of Mato Grosso do Sul, in the Brazil-Paraguay cross-border region. The conclusion of this research points out that the Brazilian and Paraguayan States, by adopting a pluralist posture, of constant dialogue with the Guarani Kaiowá, must guarantee and protect their human and fundamental rights to the territory and culture, in line, particularly, with the Constitution. of the Federative Republic of Brazil of 1988, with the Constitution of the Republic of Paraguay of 1992 and with the American Convention on Human Rights.